Modelling the impact of bovine herpesvirus-1 seropositivity on the technical and economic performance of a pastoral-based suckler beef system. (14th August 2018) - Lynch, R.; Kenny, D. A.; Parr, M. H.; Barrett, D.; Kelly, A. K.; Crosson, P.
Abstract: Bovine herpes virus 1 (BHV-1) manifests as a latent viral infection putatively affecting bovines. Understanding its effect on cattle herds is critical to maintaining sustainable beef and dairy production systems, as well as aiding in the development of herd health policies. The primary objective of the current study was, therefore, to use a whole-farm bio-economic model to evaluate the effect of herd seroprevalence to BHV-1 on the productive and economic performance of a spring calving beef cow herd. As part of a wider epidemiological study of herd pathogen status, a total of 4240 cows from 134 spring calving beef cow herds across the Republic of Ireland were blood sampled to measure the seroprevalence to BHV-1. Using data from a national breeding database, productive and reproductive performance indicators were used to parameterize a single year, static and deterministic whole-farm bio-economic model. A spring-calving, pasture-based suckler beef cow production system with an emphasis on calf-to-weanling production was simulated. The impact of BHV-1 seropositivity on whole-farm technical and economic performance was relatively small, with a marginal drop in the net margin of 4% relative to a baseline seronegative herd. Subsequent risk factors for increased pathogenicity were considered such as total herd size, percentage of intra-herd movements and vaccination status for BHV-1. In contrast to all others, scenarios representing herds that were either small in size or those which indicated an active vaccination policy for BHV-1 had no reduction in net margin against the baseline as a result of seropositivity to BHV-1.